USM TO OFFER FLEXIBLE EDUCATION WITH DOUBLE DEGREE PROGRAMMES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 20 September 2016 Second year students of Universiti Sains Malaysia (USM) who are pursuing a Bachelor’s degree full time in the university can now earn a second Bachelor’s degree in another field of study as a result of the implementation of flexible education beginning this academic year.